Renewable Fuel for Transportation Engines - R., Mamat (2019)
The current number of all vehicles on the globe reach more than 1.2 billion vehicles. These vehicles which mainly operated with internal combustion engine consume a lot of fossil fuel and contribute to air pollution and global warming. Moreover, it also causes some health disease and genetic problems. - Plenary Speaker